1995
DOI: 10.1002/jlb.57.6.805
|View full text |Cite
|
Sign up to set email alerts
|

CAP37, a neutrophil-derived multifunctional inflammatory mediator

Abstract: Cationic antimicrobial protein of M(r) 37 kDa (CAP37) is a multifunctional protein isolated from the granules of human neutrophils, which has important implications in host defense and inflammation. CAP37 was initially recognized for its strong antibiotic activity against Gram-negative bacteria and was viewed as a component of the oxygen-independent killing mechanism of the neutrophil. However, we now know that CAP37 has more far reaching and important functions. It is a physiological protein released during i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(59 citation statements)
references
References 70 publications
4
55
0
Order By: Relevance
“…Our investigations demonstrated that HBP is more readily mobilized than elastase, a protein closely related to HBP and known to be a component of azurophilic granules. 5 This finding is in line with reports from Pereira et al, 11,17 who found a massive release of HBP from neutrophils phagocytosing Staphylococcus aureus, whereas only minor amounts of CAP57 (cationic antimicrobial protein of molecular mass 57 kd also known as BPI (bactericidal permeability increasing protein) was secreted, which is stored in azurophilic granules. In Pereira et al's 17 study, however, no characterization of the compartments that contain HBP was performed.…”
Section: Discussionsupporting
confidence: 85%
“…Our investigations demonstrated that HBP is more readily mobilized than elastase, a protein closely related to HBP and known to be a component of azurophilic granules. 5 This finding is in line with reports from Pereira et al, 11,17 who found a massive release of HBP from neutrophils phagocytosing Staphylococcus aureus, whereas only minor amounts of CAP57 (cationic antimicrobial protein of molecular mass 57 kd also known as BPI (bactericidal permeability increasing protein) was secreted, which is stored in azurophilic granules. In Pereira et al's 17 study, however, no characterization of the compartments that contain HBP was performed.…”
Section: Discussionsupporting
confidence: 85%
“…13,45,46 All 3 proteins were previously shown to have monocyte-activating properties. We have earlier demonstrated that HBP activates monocytes via ␤ 2 -integrins, leading to Ca 2ϩ mobilization, 47 monocyte adhesion, 27 and the release of cytokines (O.S., H.H., L.L., manuscript submitted April 2008).…”
Section: Discussionmentioning
confidence: 99%
“…HBP is known as a potent chemoattractant for monocytes (15,26,27), but may also stimulate chemotaxis of T cells and neutrophils (28,29). However, the effect on leukocyte arrest was specific for monocytes, suggesting that this molecule represents a pathway by which monocytes can be recruited selectively.…”
Section: Discussionmentioning
confidence: 99%